Corrigendum to “Domestic energy managers and their implications for future smart grids” [Energy Pol. 206 (2025) 114772] - Sonja Oliveira; Anna Chatzimichali; Faezeh Bagheri-Moghaddam; Ed Atkins; Lidia Badarnah (Energy Policy, 2026)

Reframing Green Prosperity: integrating sustainability and just transitions into Community Wealth Building - Max Lacey-Barnacle; Ed Atkins; Eleanor Radcliffe; Martin Boucher (Environmental Innovation and Societal Transitions, 2026)

Participatory approaches to climate adaptation, resilience, and mitigation: A systematic review - Meg Parsons; Naomi Joy Godden; Karen Paiva Henrique; Petra Tschakert; Noémi Gonda; Ed Atkins; Karin Steen; Roa Petra Crease (Ambio, 2025)
For decades, social scientists and activists have advocated for equal participation of citizens in decision-making about development and equitable futures. The urgency of this call has intensified with the climate emergency, pushing communities towards resilience. Yet, the concept of participation remains contested. This systematic review examines 187 articles to understand how participatory processes in climate mitigation, adaptation, and resilience initiatives engage with power dynamics. Findings are categorised into three themes: domination and exclusion, negotiation and contestation, and transformation and emancipation. Results reveal that most participatory approaches sustain power imbalances and exclude marginalised groups, hindering meaningful engagement. However, some cases highlight transformative practices that foster empowerment, shared decision-making, and inclusivity. These examples offer pathways to rethink participatory climate action by emphasising power redistribution and community leadership. Future climate initiatives must prioritise these transformative dimensions to disrupt entrenched inequalities and achieve just and resilient outcomes.

The hidden work of everyday decisions in the home - Domestic energy managers and their implications for future smart grids - Sonja Oliveira; Anna Chatzimichali; Faezeh Bagheri-Moghaddam; Ed Atkins; Lidia Badarnah (Energy Policy, 2025)